2020
DOI: 10.1101/2020.11.02.365130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and functional plasticity in the dorsolateral geniculate nucleus of mice following bilateral enucleation

Abstract: Within the nervous system, homeostatic mechanisms stabilize network activity following disruption by injury, disease, or degeneration. Vision loss and optic nerve injury in age-related diseases such as glaucoma might trigger homeostatic responses in direct retinal projection targets in the brain in adulthood. We tested this possibility using patch-clamp electrophysiology, optogenetics, and single-cell dendritic analysis to probe the effects of optic nerve injury and vision loss on dLGN thalamocortical (TC) rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 108 publications
(199 reference statements)
0
12
0
Order By: Relevance
“…Previous work from our laboratory and others have demonstrated that superficial NGF cells receive thalamic inputs early (De Marco García, Priya et al 2015, Che, Babij et al 2018). Despite their positioning in superficial cortex, by P15 NGF cells are receive bottom-up activity.…”
Section: L1 Ngf Cells Receive Early Thalamic Inputsmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous work from our laboratory and others have demonstrated that superficial NGF cells receive thalamic inputs early (De Marco García, Priya et al 2015, Che, Babij et al 2018). Despite their positioning in superficial cortex, by P15 NGF cells are receive bottom-up activity.…”
Section: L1 Ngf Cells Receive Early Thalamic Inputsmentioning
confidence: 85%
“…As enucleation must result in considerable indirect effects through its impact on other areas of the visual system (Williams, Reese et al 2002, Nahmani and Turrigiano 2014, Rose, Jaepel et al 2016, Jaepel, Hübener et al 2017, Bhandari 2020, Hooks and Chen 2020), we wished to see if selective manipulation of the thalamic inputs that specifically project to L1 result in a similar phenotype. To do so, we injected AAV helpers together with RV-FlpO-mCherry virus in NDNF-dgCre pups and followed that with an injection of a Flp -dependent diphtheria toxin subunit A (DTA) in the dLGN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of visual deprivation on dLGN relay cell dendritic trees has also been characterized. Both in a mouse model of glaucoma or in mice lacking retinal ganglion cells axons, dendritic trees of surviving relay cells end up showing a strong reduction in size and complexity after an eventual intermediary phase of exuberant branching [69][70][71]. Altogether, developmental and deprivation studies show that retinogeniculate projections have a trophic and necessary role to establish and maintain the morpho-functional complexity of dLGN neurons.…”
Section: Structural Plasticity In the Dlgnmentioning
confidence: 99%
“…The effect of visual deprivation on dLGN relay cell dendritic trees has also been characterized. Both in a mouse model of glaucoma and in mice lacking retinal ganglion cells axons, dendritic trees of surviving relay cells ended up showing a strong reduction in size and complexity after an eventual intermediary phase of exuberant branching [70][71][72]. Similarly, albinism or dyslexia reduces the size of the dLGN [73,74].…”
Section: Structural Plasticity In the Dlgnmentioning
confidence: 99%